PENERAPAN MODEL PEMBELAJARAN AUDITORY INTELLECTUALLY REPETITION (AIR) DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN SEJARAH KELAS XI IPS DI SMA NEGERI 2 PEKANBARU - Endah Septiana, Patricia; Bunari, Bunari; Al-Fiqri, Yanuar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The results of observations at SMA Negeri 2 Pekanbaru show that student learning outcomes are not optimal. This study uses a Cooperative learning model, namely Auditory Intellectually Repetition (AIR) to improve student learning outcomes in history learning. The purpose of the learning model is an effective approach to improve student learning outcomes, helping students understand the material in depth and remember it in the long term. The type of research is classroom action research (CAR) which is carried out in two cycles. Each cycle consists of 4 stages, namely: planning, implementation, observation, and reflection. The results of this study indicate that 1) teacher activity in cycle I obtained an average of 60.00% with the criteria of "sufficient", then increased further in cycle II by 90.00% with the criteria of "very good"; 2) student activity in cycle I reached an average of 46.50% with the criteria of "sufficient", and increased in cycle II by 85.83% with the criteria of "very good"; 3) Student learning outcomes in cycle I only reached 33.00%, with 10 students completing the course. This increased to 93.00% in cycle II, with 28 students completing the course. Therefore, using the auditory intellectual repetition learning model can improve student learning outcomes in history.